Sustainable development and solid waste management : people's attitudes in Lusaka, Zambia - Shalala-Mwale, Nawa (2008)
Zambia is one of the countries in Africa with a high rate of waste generation. It has been argued that high rate of waste generation in Zambia and particularly Lusaka, its capital, is due to high population growth caused by rural-urban, urban-urban migration and natural growth. Poor waste management in the city of Lusaka has resulted in loss of people's lives due to the outbreak of diseases like cholera and dysentery. Management of waste has both positive and negative impact on sustainable development and the negative impact can only be reduced if the efforts from all stakeholders are put together to ensure solid waste is well managed. However, whilst some efforts are being made by the local authority and other stakeholders to ensure that there is sound solid waste management in the city, the contribution to this fight by the local people seems to be minimal. The main purpose of this paper was to investigate the attitudes of people in Lusaka towards waste management and to assess the role of the stakeholders. The study obtained its findings through focus group discussions of the Lusaka residents, individual interviews for the stakeholders of waste management in the city and literature review. The main findings of the study suggest that the residents see the Lusaka City Council as being exclusively responsible for waste management while at the same time the council and other stakeholders face challenges of lack of public’ support and inadequate human and financial resources to carry out their programs. The findings of this study may help relevant government bodies in the planning and decision making process for developmental projects in general and particularly in development of strategies and systems for sound management of solid waste.